The Role of Leadership and Governance in Managing Occupational Stress in Higher Educational Institutions (Impact: Journal of Transformation, 2018)
Stress is a modern-day epidemic that calls for urgent attention and proactive measures to end its threat on employees’ wellbeing in order to promote quality education through competent and reliable personnel to fulfil organizational goals. It is observed that many potential workers are severely affected as a result of occupation stress. The role of leaders in higher educational institutions and government policy makers is critical in ensuring the safety of employees in the workplace. This study is based on quantitative research methods conducted in one private university in Kenya to determine the effect of stress on workers’ effectiveness. Pertinent data was collected through a questionnaire based on open and close-ended questions. Descriptive survey design was used to describe the cause of occupational stress while correlation analysis was used to test the linear relation between variables. The results obtained from the data revealed four causes of occupational stress: Conflicting relationships among co-workers and their immediate supervisors, heavy workloads with deadlines, lack of rest, and lack of adequate finances to pay workers in due time. The outcome of the hypothesis test indicates that conflicting relationships between staff members and their immediate supervisors has a significant effect on job performance. Also, a heavy workload that needs to be accomplished within a specific period has a significant effect on job performance. Thus, it was recommended that leaders should minimize stress in the workplace by lowering the amount of work assigned, and to build strong relationships through team building activities.